Additional clinical impact of plaque analysis for on-site CT-derived FFR in coronary CT angiography on midterm prognosis. (3rd October 2022) - Nozaki, Y; Fujimoto, S; Takahashi, D; Kawaguchi, Y O; Kudo, A; Aoshima, C; Kamo, Y; Takamura, K; Hiki, M; Dohi, T; Tomizawa, N; Minamino, T
Abstract: Background: We previously reported that per-patient on-site computed tomography-fractional flow reserve (CT-FFR), which can be acquired on-site workstation using fluid structure interaction during the multiple optimal diastolic phases measured 1 to 2 cm distal to a target lesion may be feasible for risk stratification based on future cardiac events for patients who did not undergo planned revascularization. However, per-vessel CT-FFR and the additional impact of plaque analysis on CT-FFR have not been evaluated. Purpose: The aim of this study is to assess the clinical and additional impact of novel plaque analysis using labeling method for per-vessel CT-FFR on midterm prognosis. Methods: A total of 254 consecutive patients with 354 vessels showing 50–90% stenosis but not revascularized within 90 days from coronary CT angiography (CCTA) on 320-row CT were retrospectively analyzed and followed during a median follow up 3.6 years. Plaque characteristics by labeling method (necrotic core/total plaque volume (% necrotic core), non-calcified plaque (NCP)/vessel volume (%NCP), and total plaque/vessel volume (%total plaque) for both total vessel volume (mm 3 ) and at minimum lumen area (MLA, mm 2 )), positive remodeling (PR) and CT-FFR were analyzed on per-target vessels. The endpoint was vessel oriented-composite outcome (VOCO), including cardiac death, non-fatal MI, and unplanned revascularization. Results: The incidence of VOCO occurred in 6.8% (24/354). In the cox proportional hazard model, a multivariate analysis identified CT-FFR≤0.80 was the most associated factor with VOCO (all values <0.01 for other plaque morphologies), but %necrotic core, %NCP, %total plaque at MLA and PR were significantly independent of CT-FFR≤0.80. (%necrotic core HR; 3.43 (p<0.01 [95% confidence interval (CI) 1.42–8.29]), %NCP HR; 4.05 (p=0.03 [95% CI 1.19–13.71]), %total plaque at MLA HR; 2.82 (p=0.02 [95% CI 1.18–6.76]), and PR HR; 2.90 (p<0.01 [95% CI 1.30–6.51]), respectively.) Conclusion: From a view point of clinical outcomes for vessels with moderate to severe stenosis but not revascularized at initial CCTA, CT-FFR demonstrated the significant impact on per-vessel analysis. Moreover, %necrotic core, %NCP and %total plaque at MLA analyzed by labeling method provided better prognostic value in addition to CT-FFR. Funding Acknowledgement: Type of funding sources: None.